The detection of magnetic field from Partial Discharge (PD) signal in XLPE cable using inductive probe - Ghani A.B.A.; Chakrabarty C.K. (2023)
Partial discharge is a well known phenomenon that caused insulation degradation in cross-linked polyethylene power cable. Thus eventually will cause insulation failure. When partial discharge occurs, it radiates electromagnetic field in all direction. This electromagnetic field has a bandwidth of about 1GHz at source. This paper hence describes the design of a simple single layer air-core coil as inductive probe to detect the presence of magnetic field components due to partial discharge. It is shown that, it is possible to detect the presence of PD at 1m away from the cable.